2013
DOI: 10.1002/cncr.28055
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma antigen

Abstract: on behalf of the Mount Vernon Colorectal Cancer Network BACKGROUND: The objective of this retrospective study was to investigate the predictive value of pretreatment serum squamous cell carcinoma antigen (SCCAg) levels in 174 patients with squamous cell carcinoma of the anus who received concurrent chemoradiation between 1997 and 2010. METHODS: Pretreatment serum SCCAg measurements in patients with histologically diagnosed squamous cell carcinoma of the anal canal and margin who received chemoradiation were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…With respect to anal cancer, levels at baseline have been reported to have prognostic value. Specifically 49% of 174 patients demonstrated raised plasma SCCA (Williams et al , 2013) at presentation, correlating with reduced complete response to treatment and reduced disease-free and OS. More recently there has been interest in SCCA in follow up where one small study of 24 patients was not consistent with respect to baseline prognosis, but during follow up, 2 patients demonstrated a rise of SCCA, one of whom developed recurrence and metastatic disease (Henkenberens et al , 2016).…”
Section: Plasma-based Monitoring Of Diseasementioning
confidence: 99%
“…With respect to anal cancer, levels at baseline have been reported to have prognostic value. Specifically 49% of 174 patients demonstrated raised plasma SCCA (Williams et al , 2013) at presentation, correlating with reduced complete response to treatment and reduced disease-free and OS. More recently there has been interest in SCCA in follow up where one small study of 24 patients was not consistent with respect to baseline prognosis, but during follow up, 2 patients demonstrated a rise of SCCA, one of whom developed recurrence and metastatic disease (Henkenberens et al , 2016).…”
Section: Plasma-based Monitoring Of Diseasementioning
confidence: 99%
“…Serologic tumour markers have been used to diagnose and manage the follow-up treatment of head and neck cancer. The squamous cell releases a predominant squamous cell carcinoma antigen (SCC-Ag), its presence elevated in cancer patients and SCC-Ag has shown to be a promising tumour marker with squamous cell-related cancers such as gynaecologic, lung, oesophageal and anal cancers [3,4]. Considering head and neck cancer, higher levels of SCC-Ag have been associated with disease metastasis, recurrence and mortality as attested in different studies with cancer patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…SCC-Ag is a serological marker of tumor-associated antigen and is derived from the tissues of squamous cell carcinoma [6]. Previous studies reported that serum SCC-Ag level was related to the tumor stage, tumor size, depth of invasion, parametrial invasion, and lymph node metastasis in patients with cervical squamous cell carcinoma, and was an independent indicator of patient's response to treatment [7e10].…”
Section: Introductionmentioning
confidence: 99%